Land plants in the Devonian Villavicencio formation, Mendoza Province, Argentina - Edwards, D. (2001)
Plant assemblages are described from two localities, San Isidro Creek and Vaqueria, in the marine basal Devonian Villavicencio Formation in Mendoza Province, the Argentine Precordillera. Abundant smooth and more rarely axes with enations occur with rare fertile specimens and isolated swollen structures interpreted as sporangia. Sterile 'leafy' axes are placed in a new morphotaxon, Bowerophylloides, and a new genus, Isidrophyton, has been erected to accommodate sterile axes with vertically elongate, fusiform surface features and terminal sessile sporangia borne in pairs. The plants are at similar grades of organisation to those in coeval assemblages elsewhere, but cannot be assigned unequivocally to existing taxa. The locations of these Lochkovian assemblages are plotted on basal Devonian palaeocontinental reconstructions and it is concluded that the composition and the isolated position of the Argentina assemblages on the western margin of Gondwana at mid latitudes in a possibly cool temperate climate hint at a distinct phytogeographic unit. © 2001 Elsevier Science B.V. All rights reserved.